The Role of Percussion in Orchestration and Arrangement in Modern Music (International Journal of Scientific Research and Management (IJSRM), 2025)
The position of percussion in cutting-edge orchestration and arrangement has advanced notably from its conventional rhythmic features to end up a principal expressive and structural element in modern-day tune. This paper explores the development and utilization of percussion contraptions in numerous musical contexts, together with orchestral, film, famous, and experimental tune. Through a historical evaluation, theoretical evaluation, and case studies of selected works, the research investigates how percussion contributes to texture, colour, rhythm, and dynamics. The paper additionally addresses technological innovations, global impacts, and the consequences for composers and arrangers seeking to harness the total capability of percussive factors in their paintings.